Temporal variations of δ13C-CH4 in rice paddies dominated by the plant-mediated pathway - Ji Li; Huilin Chen; Aijun Ding; Xuguang Chi; Weimin Ju; Yongguang Zhang; Philippe Ciais; Wenping Yuan; Shushi Peng; Zeqing Ma; Guirui Yu; Jing M. Chen (iScience, 2025)
Summary: The stable carbon isotope signature of methane (δ13C-CH4) helps constrain CH4 emissions on regional to global scales, yet observations in rice paddies remain limited. The temporal dynamics of δ13C-CH4 and its drivers in rice paddies are still not fully understood. Here, we conducted continuous in situ observations of CH4 and δ13C-CH4 at three canopy heights throughout a rice growing season. We investigated the emission source signature (δ13Csource) and partitioned it into plant-mediated (δ13CP) and non-plant-mediated (δ13CNP) pathways. δ13Csource exhibited significant temporal and vertical variability, influenced by transport pathways and external sources. We found that temporal variations in δ13Csource were strongly correlated with rice photosynthesis and predominantly driven by δ13CP. Our results show that plant-mediated transport, rather than CH4 production, dominates δ13Csource variability. These findings provide new insight into the δ13Csource dynamics in rice paddies and will be crucial for improving regional-to-global estimates of CH4 fluxes from rice agriculture.